If your question means:
Prove sin² ( π / 8 + A / 4 ) - sin² ( π / 8 - A / 4 ) = ( 1 / √2 ) ∙ sin ( A / 2 )
then use identity:
sin² α - sin² β = sin ( α + β ) ∙ sin ( α - β )
In this case:
α = π / 8 + A / 4 , β = π / 8 - A / 4
so
sin² ( π / 8 + A / 4 ) - sin² ( π / 8 - A / 4 ) =
sin ( π / 8 + A / 4 + π / 8 - A / 4 ) ∙ sin [ π / 8 + A / 4 - ( π / 8 - A / 4 ) ] =
sin ( π / 8 + π / 8 ) ∙ sin ( π / 8 + A / 4 - π / 8 + A / 4 ) =
sin ( 2 π / 8 ) ∙ sin ( A / 4 + A / 4 ) = sin ( π / 4 ) ∙ sin ( 2 A / 4 ) =
sin ( π / 4 ) ∙ sin ( A / 2 ) = ( 1 / √2 ) ∙ sin ( A / 2 )
Sin^2(π\8+A/4)-sin^2(π\8-A/4)=1/√2sinA/2
2 answers
Remark:
π / 4 rad = 45°
sin ( π / 4 ) = sin 45° = √2 / 2 = √2 ∙ 1 / √2 ∙ 2 = 1 / √2
This means √2 / 2 is the same as 1 / √2
π / 4 rad = 45°
sin ( π / 4 ) = sin 45° = √2 / 2 = √2 ∙ 1 / √2 ∙ 2 = 1 / √2
This means √2 / 2 is the same as 1 / √2